Trust in co-workers as a mediator of co-workers' trustworthiness, social undermining behaviour, and job performance / Ong Lin Dar - Ong, Lin Dar (2011)
This study tested whether the relationship between perceptions of co-workers’ trustworthiness and employees’ job performance is mediated by trust in co-workers. The study also examined the extent to which trust in co-workers mediates the relationships between co-workers’ social undermining behaviour and employees’ job performance. All the measures were adopted from the work of past authors. The items were altered slightly to reflect the reference to co-workers. Three structured questionnaires were designed to collect data from employees, their co-workers, and immediate supervisors. There were 502 employees from ten organisations in Malaysia that participated in the survey. The IBM SPSS Statistics 17 was used to perform the item-total correlations analysis, Exploratory Factor Analysis (EFA), reliability test and correlation analysis. The IBM SPSS AMOS 18 was also used to test the hypotheses of this study. The SEM analysis showed that co-workers’ benevolence, integrity, and social undermining behaviour had indirect relationships with employees’ job performance via the mediating role of trust in co-workers. The findings suggested that co-workers’ positive attributes and negative behaviour could influence employees’ job performance through the mediating role of trust in co-workers. The results of this study highlighted the importance of being benevolent and possessing integrity as well as curbing social undermining behaviour in the workplace in order to instil trust among employees and better job performance. When employees perceived their co-workers as trustworthy, they would trust their co-workers, and in turn they would likely engage in more organisational citizenship behaviour and less counterproductive work behaviour, as well as give better task performance.